METODOLOGI DAN KRITERIA KRISTOLOGI - Cintya Fioni; Liska Meri Monika, Riri Handriani, Shinta, Sarmauli (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This research aims to explore the understanding of Christology in the daily lives of Christians in the modern era and its implications for faith growth. Within the context of pluralism, secularism, and technological advancement, the challenge is to uphold the authentic teachings of Christ. The research method employs a qualitative approach through literature study, in-depth interviews with theologians and congregants, and participatory observation in church activities. The findings reveal that a correct understanding of the person of Jesus Christ as both God and man is highly relevant in shaping the faith identity of Christians. Furthermore, the research illustrates how Christological teachings can be applied in everyday life, encouraging acts of love, integrity, and attention to social issues. Thus, Christology serves not only as a theological study but also as a practical guide for Christians to face contemporary challenges and effect positive change in society.